George M. Duck Lecture - Naqvi, Yasir (Windsor Yearbook of Access to Justice / Recueil annuel de Windsor d'accès à la justice)

(untitled) (Faculty of Law, University of Windsor, 2018)
The Hon. Yasir Naqvi, Attorney General of Ontario, delivered the George M. Duck Lecture at the University of Windsor Faculty of Law on February 28, 2018.